9514 1404 393
Answer:
Step-by-step explanation:
The outside factor multiplies each term in parentheses.
a) 2(b+c) = 2b +2c
b) 5(7h +3m) = 5×7h +5×3m = 35h +15m
c) e(f +g) = ef +eg
Answer:
72 I think
Step-by-step explanation:
I'm not 100% sure but I think its 72
Answer:
<h3>Figure 1</h3>
- Perimeter of base = 5 + 5 + 8 = 18 ft
- Base area = 1/2(8)(3) = 12 ft²
<u>Surface area:</u>
- S = 18*7 + 2*12 = 150 ft²
<h3>Figure 2</h3>
<u>Surface area of cube:</u>
- S = 6a² = 6(2.5)² = 37.5 m²
<u>Surface area of prism:</u>
- S = 2(11 + 9)(7) = 280 m²
<u>Overlapping area:</u>
<u>Surface area of composite figure:</u>
- S = 280 + 37.5 - 2(6.25) = 305 m²
Answer:
Step-by-step explanation:
(-2x-3)(4x+5) = -(2x+3)(4x+5) = -(8x^2+12x+10x+15) = -8x^2 - 22x - 15
Leading coefficient is -8
Answer:
680
Step-by-step explanation:
125 + 215 = 340
340+340 = 680